PEMBELAJARAN MENULIS TEKS BIOGRAFI MENGGUNAKAN MEDIA WORLDWALL PADA SISWA KELAS X SMA: STUDI KUALITATIF DESKRIPTIF - Nainggolan, Mira Wati; Rustam, Rustam; Wini, Lusia Oktri (Penerbit Widina, Widina Media Utama, 2026)
Learning to write biographical texts for grade X senior high school students still faces various obstacles, such as difficulties in developing content, structuring the text, and formulating messages from the character's life. Therefore, innovative learning media are needed to assist students in the writing process. This study aims to describe the learning process of writing biographical texts using Wordwall media for grade X senior high school students. This study uses a qualitative method with a descriptive approach. The subjects of the study were grade X senior high school students, while data were obtained through observation, biographical text writing tests, and documentation. Data analysis was carried out by describing the learning process and students' writing results after the application of Wordwall media. The results of the study indicate that Wordwall media is able to increase students' activeness and motivation in learning to write biographical texts. Students more easily understand the structure of the text, the appropriateness of the content, and the message of the character's life, although some students still experience difficulties in developing ideas. In general, the use of Wordwall is considered quite effective and able to create a more interesting learning experience.ABSTRAKPembelajaran menulis teks biografi pada siswa kelas X SMA masih menghadapi berbagai kendala, seperti kesulitan mengembangkan isi, menyusun struktur teks, dan merumuskan pesan kehidupan tokoh. Oleh karena itu, diperlukan media pembelajaran yang inovatif untuk membantu siswa dalam proses menulis. Penelitian ini bertujuan untuk mendeskripsikan pembelajaran menulis teks biografi menggunakan media Wordwall pada siswa kelas X SMA. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Subjek penelitian adalah siswa kelas X SMA, sedangkan data diperoleh melalui observasi, tes menulis teks biografi, dan dokumentasi. Analisis data dilakukan dengan mendeskripsikan proses pembelajaran dan hasil tulisan siswa setelah penerapan media Wordwall. Hasil penelitian menunjukkan bahwa media Wordwall mampu meningkatkan keaktifan dan motivasi siswa dalam pembelajaran menulis teks biografi. Siswa lebih mudah memahami struktur teks, kesesuaian isi, dan pesan kehidupan tokoh, meskipun sebagian siswa masih mengalami kesulitan dalam mengembangkan gagasan. Secara umum, penggunaan Wordwall dinilai cukup efektif dan mampu menciptakan pengalaman belajar yang lebih menarik.